PRELIMINARY ROOTING STUDY OF TOMATO (Solanum lycopersicum L.) IN RESPONSE TO DROUGHT STRESS AS MANAGED BY AQUAGRAIN APPLICATION - Adnan. A. A.; Shittu, E. A.; Mansur, A. I. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
A field experiment was conducted to investigate the effects of Aquagrain application, a proteinbased SAP, on tomato root development during the 2024 dry season at the Center for Dryland Agriculture (CDA) Research and Training Farm, Kano, Nigeria. The treatment consisted of four rates of aquagrain (0, 200, 225, and 250 kg/ha) and two tomato varieties (local and improved) which were factorially combined and laid out in a randomized complete block design (RCBD) with three replications. Data were collected on plant growth and root parameters and subjected to analysis of variance (ANOVA) using GENSTAT (11th edition). Significant means were separated using the Student Newman’s’ Test (SNK). Result of the experiment revealed that, Aquagrain application improved soil moisture retention and consequently plant growth (height, leaves, branches). The most significant positive effects were observed at the highest concentration (250 kg/ha) with the improved tomato variety. These findings suggest protein-based SAPs hold promise for mitigating drought stress in tomatoes. However, further research is required to assess long-term impacts on soil quality, crop yield, and the environment alongside optimizing application rates for various crops and growing conditions.